The causes and impacts of flood risks in South Africa - Raphela, Tlou D.; Matsididi, Mollin (Frontiers in Water, 2025)
IntroductionFloods are classified as one of the hydrological hazards affecting many countries worldwide. With most weather-related disasters occurring in developing countries, demographics and socioeconomic pattern changes have contributed to many losses relating to water-related disasters such as floods. South Africa is among the developing countries most frequently affected by natural disasters, particularly floods. Thus, this study assessed the causes and impact of floods on the communities of Bronville and Hani-park in Welkom in the Free State Province in South Africa.MethodsThe study adopted a quantitative approach, using a structured questionnaire to collect the data. The study used an R statistical package to analyze the data and applied descriptive statistics and a series of Generalized linear models to examine the impacts of floods in the community.ResultsThe findings reveal a community-wide concern about flooding impacts. There was a statistically significant difference between whether floods affected your physical structure as an outcome variable and how the flooding affected participants (Wald χ62 = 30.364; p = 0.001). Also, a significant difference was found regarding how floods affect the water quality in your community (Wald χ2 = 1.496; p = 0.030). The subjective perception of flood impacts on households has been reported to be aligned with observed damage to physical structures, underscoring the direct influence of floods on various household elements. The study also emphasises the costly nature of flood recovery and the potential strain on household resources due to flooding. Respondents indicated floods adversely affect vegetation, soil stability, and ecological dynamics. he study also, reveals that while some residents affected by flooding reach out to their municipalities for support, many do not seek or receive financial assistance.DiscussionThe study concludes that floods have a considerable socioeconomic impact on households and communities, particularly regarding repair costs for flood-related damages. In addition, the study concludes that floods have significant implications for drinking water quality in the community, with statistical evidence supporting the claim that floods contribute to water quality degradation. The findings of flood preparedness suggest a clear gap in early warning dissemination and evacuation planning tailored to the study community’s needs. The findings of this study underscore the urgent need for comprehensive and sustainable flood mitigation strategies in vulnerable communities like Bronville and Hani-park.